Pensions Policy: Evidence on Aspects of Savings Behaviour and Capital Markets - Neuberger, Anthony; McCarthy, David G (London : Centre for Economic Policy Research, 2003)
David McCarthy and Anthony Neuberger review the research that has been done internationally in the area of pensions policy.
"December 2003"
Includes bibliographical references.
rpm 22/08/16
Loans
Keywords: Pensions; Pension Trust -- Investment; Capital Market; Pensions- Europe